An Empirical Study on Adults’ Engagement in Learning in Literacy and Job Acquisition - Efua Irene Amenyah Sarr (Modern Perspectives in Language, Literature and Education Vol. 7, 2021)
This paper examines the relation between adults’ engagement in literacy and job acquisition. In literacy educational settings, adults engage and persist in learning activities for they are mainly oriented in job acquisition. We postulate that adults’ learners who achieve literacy activities, graduate within a job. To collect date, mixed method using qualitative and quantitative approaches was used. Results indicate that 90% of adult learners achieved their learning activities because they have graduated with a job they have chosen to learn and they are performing it. In sum, it is clear that when adult learners recognize that learning activities lead to exercise job, they are not only motivated to learn but they persevere as their future live depend on that job acquisition.